Breast Cancer Screening, Management, and a Review of Case Study Literature in Transgender Populations - Deutsch, Madeline B.; Radix, Asa; Wesp, Linda (Seminars in Reproductive Medicine, 2017)
Because of a lack of uniform collection of gender identity data, population-level breast cancer statistics in the transgender community are unknown. With recent estimates that at least 0.6% (1 in every 167 people) of the U.S. population is transgender, guidance on breast cancer risk, screening, and management in this population is needed. Such guidance should examine modifications, if any, to recommendations in cisgender populations, taking into consideration any history of hormone therapy exposure or breast surgery. This article describes existing evidence on breast cancer incidence in transgender women and men, and attempts to make rational recommendations regarding the screening for and approach to managing breast cancer in transgender populations. Current data are mostly limited to case reports which are reviewed here. More prospective, population-level research is needed to better understand the risks and predictors of breast cancer in this population, as well as to better inform the most appropriate screening modality, age of starting screening, and interval. Ultimately, a risk score calculator similar to existing risk models such as the Gail score, as well as an approach to shared decision making that involves patient-centered perspectives, is needed to best guide practices in this area.
Keywords: transgender; breast cancer; screening; treatment